PENGARUH WORK-LIFE BALANCE DAN BURNOUT TERHADAP KEPUASAN KERJA - Livi Pangemanan, Friane; Johnly Pio, Riane; Tumbel, Tinneke M. (Sam Ratulangi University, 2017)
The purpose of this study is to examine the influence of work-life balance and burnout on job satisfaction of the employees inÂ PT. Jasa Raharja (Persero) Branch of Sulawesi Utara. Data were collected from questionnaires completed by 32 participants and analysed using multiple regression analysis. The findings reveal that work-life balance had a positive and significant impact to job satisfaction. Further, burnout had a negative impact to job satisfaction but the result was insignificant. This study recommends the company to keep facilitate the employee in enhancing work-life balance and reducing burnout. Â Keywords: Work-life Balance, Burnout, Job Satisfaction